Mathematische Modelle in der Biologie: 15.3. bis 21.3.1987 - Werner, Helmut; Hadeler, Karl-Peter; Jäger, Willi (Tagungsbericht, 1987)
T. Aldenberg, Bilthoven; W. Alt, Bonn; B. Aulbach, Augsburg; E. Bohl, Konstanz; S. Busenberg, Claremont; P. Colli, Pavia; P. Colli-Franzone, Pavia; J. Cushing, Tucson; O. Diekmann, Amsterdam; K. Dietz, Tübingen; H. I. Freedman, Edmonton; J. P. Gabriel, Fribourg-Perolles; U. Gaedke, Konstanz; A. Grabosch, Washington D. C.; M. R. Guevara, Montreal; M. Gvllenberg, Espoo; K. P. Hadeler, Tübingen; U. an der Heiden, Witten-Annen; H. J. A. Heijmans, Amsterdam; J. Hofbauer, Wien; W. Jäger, Heidelberg; P. Jagers, Göteborg; J. P. Keener, Salt Lake City; M. Kretzschmar, Tübingen; A. Lasota, Lublin; D. Lauffenburger, Philadelphia; M. Löffler, Köln; M. C. Mackey, Montreal; J. A. J. Metz, Leiden; J. Milota, Praha; P. de Mottoni, Rom; H. G. Othmer, Salt Lake City; G. Palm, Tübingen; M. Peschel, Berlin; L. Pilz, Heidelberg; J. Rinzel, Bethesda; W. Rittgen, Heidelberg; F. Rothe, Neubiberg; R. Schaaf, Heidelberg; H. Schwegler, Bremen; K. Sigmund, Wien; B. D. Sleeman, Dundee; H. L. Smith, Tempe; B. Tang, Los Angeles; P. Tautu, Heidelberg; H. R. Thieme, Heidelberg; R. Tranquillo, Oxford; J. J. Tyson, Blacksburg; G. S. K. Wolkowicz, Hamilton
Beitr. in engl. Sprache
Keywords: Konferenzschrift